2001
DOI: 10.1007/s001270170014
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of caregivers on aspects of schizophrenia and major affective disorders in a Nigerian setting

Abstract: These families were tolerant and would cooperate with health authorities. Causative models are influenced by available knowledge and practices in the culture. To actualize the potential of families to play useful community psychosocial roles, there is a need for public mental health literacy and welfare support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 22 publications
2
45
0
1
Order By: Relevance
“…In a study on psychosocial issues in a child and adolescent psychiatric population, Omigbodun (2004a) found that beliefs in spiritual forces giving rise to mental illness led to child abandonment, physical abuse and children kept locked away for several years in traditional or religious places, out of school and suffering dire consequences. Ohaeri and Fido (2001) also found that the majority of families of sufferers of mental illness believed it was caused by spiritual forces.…”
Section: Perceptions Of Mental Health Problems In Childrenmentioning
confidence: 94%
“…In a study on psychosocial issues in a child and adolescent psychiatric population, Omigbodun (2004a) found that beliefs in spiritual forces giving rise to mental illness led to child abandonment, physical abuse and children kept locked away for several years in traditional or religious places, out of school and suffering dire consequences. Ohaeri and Fido (2001) also found that the majority of families of sufferers of mental illness believed it was caused by spiritual forces.…”
Section: Perceptions Of Mental Health Problems In Childrenmentioning
confidence: 94%
“…Large scale studies have shown that between a quarter and a half of family members believe that their relationship with a person with mental illness should be kept hidden or otherwise be a source of shame to the family (Angermeyer, Schulze, & Dietrich, 2003;OÕHaeri & Fido, 2001;Phelan et al, 1998;Phillips, Pearson, Li, Xu, & Yang, 2002;Shibre et al, 2001;Thompson & Dahl, 1982;Wahl & Harman, 1989). One study showed family shame was 40 times more prevalent in families with people with mental illness compared to families who have relatives with cancer (Ohaeri & Fido, 2001). Shame seemed to be clearly linked to blaming the family for the memberÕs psychiatric disorder.…”
Section: Stigma and Family Membersmentioning
confidence: 95%
“…Several studies from Africa have addressed the issue of the burden of care giving on families of mentally ill patients. [5][6][7][8] However, no study has been conducted in Kenya on the subjective and objective dimensions of the burden of care on relatives of psychiatric in-patients. This study aimed to fill the gap in the knowledge of the extent of this burden, and to provide suggestions for possible interventions at both policy and practice levels in the Kenyan context.…”
Section: Introductionmentioning
confidence: 99%